Structure of an F-type phage tail-like bacteriocin from Listeria monocytogenes - Zhiwei Gu; Xiaofei Ge; Jiawei Wang (Nature Communications)
Abstract F-type phage tail-like bacteriocins (PTLBs) are high-molecular-weight protein complexes exhibiting bactericidal activity and share evolutionary similarities with the tails of non-contractile siphoviruses. In this study, we present the atomic structure of monocin, a genetically engineered F-type PTLB from Listeria monocytogenes. Our detailed atomic-level analysis, excluding two chaperone proteins, provides crucial insights into the molecular architecture of F-type PTLBs. The core structure of monocin resembles TP901-1-like phage tails, featuring three side fibers with receptor-binding domains that connect to the baseplate for host adhesion. Based on these findings, we propose a potential mechanism by which F-type PTLBs induce cell death, offering a foundation for developing targeted antibacterial therapies.